2018
DOI: 10.1016/j.csbj.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Techniques of using circulating tumor DNA as a liquid biopsy component in cancer management

Abstract: Precision medicine in the clinical management of cancer may be achieved through the diagnostic platform called “liquid biopsy”. This method utilizes the detection of biomarkers in blood for prognostic and predictive purposes. One of the latest blood born markers under investigation in the field of liquid biopsy in cancer patients is circulating tumor DNA (ctDNA). ctDNA is released by tumor cells through different mechanisms and can therefore provide information about the genomic make-up of the tumor currently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
223
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(242 citation statements)
references
References 136 publications
0
223
0
1
Order By: Relevance
“…This step enriched the cfDNA sample, allowing ddPCR and sequencing to become more feasible due to the higher amount of DNA template required. Numerous NGS technologies such as BEAMing and Safe-SeqS have been used to detect known breast cancer mutations using ctDNA with sensitivity higher than 99% 30 . Our own studies have shown for primary patients that recurred, patient specific ctDNA profiling detected molecular relapse up to 2 years ahead of clinical relapse with 89% sensitivity and 100% specificity 31 .…”
Section: Discussionmentioning
confidence: 99%
“…This step enriched the cfDNA sample, allowing ddPCR and sequencing to become more feasible due to the higher amount of DNA template required. Numerous NGS technologies such as BEAMing and Safe-SeqS have been used to detect known breast cancer mutations using ctDNA with sensitivity higher than 99% 30 . Our own studies have shown for primary patients that recurred, patient specific ctDNA profiling detected molecular relapse up to 2 years ahead of clinical relapse with 89% sensitivity and 100% specificity 31 .…”
Section: Discussionmentioning
confidence: 99%
“…To address this challenge, we reconstructed tumor phylogenies from genome and exome sequencing of tissue in order to select alleles representing the major subclones that would be present at the time of surgery and further mediate relapse. Prior to executing these experiments, we developed and tested a bespoke patient-specific, allele-specific sequencing assay that satisfied requirements for reproducibility, accuracy, sensitivity, and specificity [16,30,31]. This assay consistently detected spiked-in alleles and showed 100% concordance to unbiased whole exome sequencing of the same sample at very high coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular barcoding is one of the possible solutions when dealing with challenging clinical samples since unique molecular tags, also known as unique molecular index (UMI), are added into every DNA molecule, prior to library amplification [5][6][7][8][9][10]. This has the great advantage to increase the sensitivity by keeping track of the DNA molecules intercepted, meanwhile reducing polymerase chain reaction (PCR) and/or sequencing artefacts [11][12][13][14], also when compared to amplicon-based NGS [15].…”
Section: Introductionmentioning
confidence: 99%